Psychological Well-Being Among Older Adults - Achwandi, Moch (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Psychological Well-Being (PWB) refers to the psychological state of an individual characterized by self-acceptance, positive relations, autonomy, environmental mastery, purpose in life, and personal growth (Ryff, 1989). Among older adults, PWB plays a crucial role in determining quality of life and resilience in facing physical and social changes. This study aimed to describe the level of PWB among older adults. A cross-sectional descriptive design was applied with 35 participants at a community-based elderly health post in East Java, Indonesia, during May–July 2022. Findings showed that nearly one-third of respondents (28.6%) had low levels of PWB, while only 17.1% were in the very high category. These results suggest that factors such as age, low education, and unemployment contribute to decreased PWB. Recent studies further highlight the importance of resilience, social support, religiosity, and meaningful activities as protective factors (López et al., 2020; Herdian et al., 2022; Aisyah & Chisol, 2020; MDPI, 2020). Nursing interventions should therefore address not only physical health but also psychological, social, and spiritual well-being to holistically improve the quality of life in older adults.